2018
DOI: 10.1001/jamafacial.2018.0876
|View full text |Cite
|
Sign up to set email alerts
|

Use of Routine Prospective Functional and Aesthetic Patient Satisfaction Measurements in Secondary Cleft Lip Rhinoplasty

Abstract: IMPORTANCE Patients, governments, health care providers, and insurance companies show an increased interest in health outcomes, especially in centralized medical care, such as cleft lip nose treatment. Transparent outcome reporting requires a thorough methodological design, dedicated prospective data collection process, and, preferably, no interference with the efficacy of daily practice. OBJECTIVE To describe the implementation of an automated and prospective secondary cleft lip rhinoplasty outcome routine. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…[33, 50,81,83,119,162,168,173,211]. An additional 18 studies reported mixed-methods evaluations which included interviews, focus groups, or analysis of chart notes [27,29,56,57,61,68,116,127,147,161,[177][178][179]187,192,194,204,212]; only 6 reported results of qualitative assessments of end-user perceptions of dashboards without a quantitative evaluation[28, 48,52,163,167,203](Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33, 50,81,83,119,162,168,173,211]. An additional 18 studies reported mixed-methods evaluations which included interviews, focus groups, or analysis of chart notes [27,29,56,57,61,68,116,127,147,161,[177][178][179]187,192,194,204,212]; only 6 reported results of qualitative assessments of end-user perceptions of dashboards without a quantitative evaluation[28, 48,52,163,167,203](Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…, details available in Supplementary Table9). Dashboards developed using custom coding often described use of specific programs or coding languages, including structured query language (SQL), JavaScript, and Cascading Style Sheets (CSS).Overall, dashboards were most often available to end-users as websites (n=41/118, 34.7%)[23,28,33,50,52,55,58,61,68,71,83,84,97,99,103,104,109,110,115,116,119,128,147,151,153,163,[167][168][169]171,[173][174][175]179,181,189,194,204,208,209] or as tools embedded directly into the EHR (n=17/118, 14.4%)[29,49,51,[55][56][57]69,101,107,111,124,126,127,144,148,199,211] (…”
mentioning
confidence: 99%
“…Thus, cleft rhinoplasty is regarded as a tough and vital reconstructive procedure. Several factors, such as scars from previous surgeries, insufficient soft tissue for tension-free closure, and displaced and deformed cartilage, might contribute to the final poor postsurgical results ( 16 ).…”
Section: Discussionmentioning
confidence: 99%